2013
DOI: 10.3389/fnhum.2013.00212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of individual glucose levels on the neuronal correlates of emotions

Abstract: This study aimed to directly assess the effect of changes in blood glucose levels on the psychological processing of emotionally charged material. We used functional magnetic resonance imaging (fMRI) to evaluate the effect of blood glucose levels on three categories of visually presented emotional stimuli. Seventeen healthy young subjects participated in this study (eight females; nine males; body weight, 69.3 ± 14.9 kg; BMI, 22 ± 2.7; age, 24 ± 3 years), consisting of two functional MRI sessions: (1) after an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Gonder-Frederick et al [36] reported, more than two decades ago, that hyperglycemia was associated with negative emotions (i.e., sadness, anger); a finding only recently replicated in nearly 500 healthy men [37]. Most recently, Schöpf et al [38] showed that hyperglycemia, via a glucose clamp (at 160-180 mg/L), was associated with reduced activations in limbic structures (amygdala, hippocampus, hypothalamus) to negative or positive stimuli during the hyperglycemic, compared with a euglycemic baseline, in young, healthy subjects. While an interesting finding, the hyperglycemic clamp always followed the euglycemic baseline, rendering these results vulnerable to "order" effects.…”
Section: Discussionmentioning
confidence: 95%
“…Gonder-Frederick et al [36] reported, more than two decades ago, that hyperglycemia was associated with negative emotions (i.e., sadness, anger); a finding only recently replicated in nearly 500 healthy men [37]. Most recently, Schöpf et al [38] showed that hyperglycemia, via a glucose clamp (at 160-180 mg/L), was associated with reduced activations in limbic structures (amygdala, hippocampus, hypothalamus) to negative or positive stimuli during the hyperglycemic, compared with a euglycemic baseline, in young, healthy subjects. While an interesting finding, the hyperglycemic clamp always followed the euglycemic baseline, rendering these results vulnerable to "order" effects.…”
Section: Discussionmentioning
confidence: 95%
“…With respect to carbohydrate intake and neurocognitive performance, it is well established that glucose ingestion enhances memory performance, but no such beneficial memory effect of glucose is typically observed for emotionally laden stimuli (Smith et al, 2011 ). Schopf et al ( 2013 ) report that following glucose ingestion, the hypothalamus becomes inactive in response to emotional material, providing a mechanistic explanation for the previously observed behavioral observations. Further, Jackson and Kennedy ( 2013 ) discuss the ways in which near-infrared spectroscopy has proven useful in detecting changes in cerebral blood flow following ingestion of dietary constituents including caffeine, polyphenols and omega-3 fatty acids.…”
mentioning
confidence: 80%
“…With respect to carbohydrate intake and neurocognitive performance, it is well established that glucose ingestion enhances memory performance, but no such beneficial memory effect of glucose is typically observed for emotionally laden stimuli . Schopf et al (2013) report that following glucose ingestion, the hypothalamus becomes inactive in response to emotional material, providing a mechanistic explanation for the previously observed behavioral observations. Further, Jackson and Kennedy (2013) discuss the ways in which near-infrared spectroscopy has proven useful in detecting changes in cerebral blood flow following ingestion of dietary constituents including caffeine, polyphenols and omega-3 fatty acids.…”
mentioning
confidence: 57%